Strength Analysis of Towing Hook Support Structure on TB. Khatulistiwa 01 - Philipus Valentino; Hartono Yudo; Ahmad Fauzan Zakki (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2022)
Towing hook is one of the important components of a tugboat. Its function is to tow various types of ships, namely containers, tanker ships, and even barges. This activity affects the components to undergo failure and crack, especially the support structure of the hook. Earlier research has analyzed various types of stress characteristics, namely fatigue crack, maximum stress, and maximum factor of safety aimed both at the support structure and the whole profile of the tug. The research aim is to determine the value of stress in the support structure and the safety factor brought by tensile load transferred from the towing hook. The analysis is done using finite element method in Altair Hyper Works 2019. Structural strength of the towing hook support structure is analyzed in 2 loading conditions, namely lightweight barge and full load barge. Two different approaches are used for comparison. The first approach is using barge resistance, and the second is by utilizing maximum tug horse-power to speed ratio. Maximum stress acquired in both loading conditions and both approaches is 118.64 MPa; 121.80 MPa; 230.90 MPa; 329.86 MPa respectively. The safety factor is measured using 2 criteria, BKI permissible stress criterion and BKI Material Strength criterion. Results of safety factors based on BKI permissible stress are 1.644; 1.601; 0.845; and 0.591. According to BKI Material Strength, the safety factors on both loading conditions are 3.371; 3.284; 1.732; and 1.212.